2020
DOI: 10.18632/oncotarget.27545
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SYK kinase does not confer a pro-proliferative or pro-invasive phenotype in breast epithelium or breast cancer cells

Abstract: SYK has been reported to possess both tumour promotor and repressor activities and deletion has been linked to a pro-proliferative / pro-invasive phenotype in breast tumours. It is unclear whether this is a consequence of protein deletion or loss of kinase activity. The SYK inhibitor, BI 1002494, caused no increase in proliferation in breast cancer cells or primary mammary epithelial cells in 2D or 3D cultures, nor changes in proliferation (CD1/2, CDK4, PCNA, Ki67) or invadopodia markers (MMP14, PARP, phospho-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The SYK protein appears to have a dual role: depending on the alternative splicing of the mRNA it may act as a pro-oncogene or a tumor suppressor protein, and can interact differentially with its targeted genes [ 25 ]. The mechanisms surrounding this dual role of the SYK protein are still being largely studied [ 26 ]. Here, the multi-omics hive plots and bi-partite networks provided by MiBiOmics can be useful to generate new hypothesis on the associations and potential interactions between SYK and specific genes and miRNAs linked in the multi-omics network.…”
Section: Resultsmentioning
confidence: 99%
“…The SYK protein appears to have a dual role: depending on the alternative splicing of the mRNA it may act as a pro-oncogene or a tumor suppressor protein, and can interact differentially with its targeted genes [ 25 ]. The mechanisms surrounding this dual role of the SYK protein are still being largely studied [ 26 ]. Here, the multi-omics hive plots and bi-partite networks provided by MiBiOmics can be useful to generate new hypothesis on the associations and potential interactions between SYK and specific genes and miRNAs linked in the multi-omics network.…”
Section: Resultsmentioning
confidence: 99%
“…SYK was found to possess the promotor and repressor activities of breast cancers. David J Lamb et al found the SYK inhibitor BI1002494 showed no increased proliferation of breast cancer cells 36 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared with normal tissues, the brain tumors and breast tumors hold much higher expression of SYK, while the level of SYK is lower in leukemia and lymphoma [ 44 ]. Even though lots of studies have indicated that SYK negatively regulates cell proliferation and migration in cancer cells, lots of SYK inhibitors are considered as promising anti-cancer drugs in both clinical studies and pre-clinical studies [ 1 , 19 , 57 , 58 ]. Especially, based on the important function of SYK in hematopoietic cells, the therapeutic action of SYK inhibitors has been confirmed in multiple myeloma, such as acute myeloid leukemia and chronic lymphocytic leukemia [ 1 , 59 , 60 ].…”
Section: The Relationship Between Syk and Different Liver Diseasesmentioning
confidence: 99%